The use of Oil Shale in Cement Manufacturing (Global Journals of Research in Engineering, 2024)
The world s strong economic growth and increasing populations have generated a remarkably growing demand for resources especially energy Current conventional sources cannot meet the future needs Efforts are being focused on renewable energies deep-sea oil and the development of new techniques to value heavy oils tar sands and oil shale This could bridge the gap between energy demand and supply In our study and research program we have developed solutions to exploit oil shale deposits as part of sustainable development using renewable energy sources unconventional water and CO2 capture techniques in addition to the integration of other uses The objective is to make the overall exploitation of oil shale deposits profitable remarkably reducing the impact on the global environment To make the exploitation of oil shale deposits profitable our research was directed towards the development of other possibilities of use concerning the coating of roads and runways the production of cement and the manufacture of carbon plates In this article we develop the use of shale for cement manufacturing
Keywords: oil shale; coating of roads; sustainable development; cement manufacturing; deposits resources